SARS-CoV-2 pandemic as a catalyst? Development of emotional problems of preschool children of mothers with childhood maltreatment experiences in the course of the pandemic–a longitudinal analysis - Dalhof, Manuela (Gulde); Rost, Katharina; Ziegenhain, Ute; Fegert, Jörg M.; Köhler-Dauner, Franziska (Frontiers in Pediatrics, 2023)
Background SARS-CoV-2 pandemic have posed great challenges for all families and children. Health risks and fears associated with SARS-CoV-2 negatively affect the parental mental health and perceived stress, which in turn influence parental coping and thereby impairs the mental health and well-being of their children. Additional risk factors within the parents, such as maternal childhood maltreatment (CM) experiences, may increase the risk of children to develop emotional problems during the pandemic. Objective The purpose of this longitudinal study is to determine whether preschool children of mothers with CM are at higher risk of developing emotional problems during the pandemic than preschool children of mothers without CM. Method 74 mothers from a birth cohort examining pathways to resilience or vulnerability in the transgenerational transmission of CM, provided information on emotional problems of their children (aged 3–7 years) at two measurement time points (t1: May 2020, t2: March 2021) as part of an online “SARS-CoV-2 pandemic” survey. In addition, parents were asked for a retrospective assessment of their children's emotional problems before the pandemic at time t1. Children's emotional problems were assessed using the “emotional problems” scale of the German version of the Strengths and Difficulties Questionnaire (SDQ) and linked to previously collected data on mothers' childhood maltreatment experiences, which were collected using the German short version of the Trauma in Childhood Questionnaire (CTQ). Results Our analyses showed that children's emotional problems increased significantly over the SARS-CoV-2 pandemic [F(1.86, 116.88) = 3.72, p = 0.030 η2 = 0.06] and were rated significantly higher in the group of children of mothers with CM, than in the group of mothers without CM [F(1, 63) = 126.06, p < 0.001 η2 = 0.67]. Furthermore children's emotional problems of mothers with CM increased significantly more and reached a clinically significant value during the pandemic than for children of mothers without CM [F(1.86, 116.88) = 8.89, p < 0.001, η2 = 0.12]. Conclusions Children of mothers with CM appear to be at increased risk of developing emotional problems during the pandemic. CM therefore needs to be considered as an additional risk factor in the impact of the pandemic on children.